Evaluası Penggunaan Obat Pasıen Penyakıt Jantung Koroner Pasca Pemasangan Stent dı RSPAD Gatot Soebroto - Alika Khansa Adita; Wan Syurya Tri Dharma (Journal Borneo, 2023)
Coronary Heart Disease (CHD) occurs when the coronary arteries are narrowed by a buildup of atheroma and fatty material in the walls. Stent placement is done to treat narrowed coronary arteries and an option if the patient has tried medication or lifestyle changes but fails to improve heart health and has blockages in the arteries. This study aims to evaluate the 4 medication usage accuracies, to determine the characteristics and medication usage profiles in CHD patients after stent placement at Gatot Soebroto Hospital. This research was conducted with analytical descriptive and retrospective data collection through medical records for the 2021 period. The sample used was 83 patients. The study resulted based on the characteristics the most patients with CHD after stent placement were aged <65 years with 57 patients (68.68%), and the most comorbid hypertension was 26 patients (31.32%). The medicine widely used in CHD patients after stent placement is a combination of aspirin and clopidogrel in as many as 70 patients (83.34%). The parameters of the medication usage accuracy, the right indication, the right medicine, the right dose, and the right patient resulted in 100% that the patient got the suitability for medication use. The results of the relationship between variables and medication use through SPSS showed that gender had a sig value of 0.051 (>0.005), age had 0.544 (>0.005), and risk factors had 0.167 (>0.005) means that there is no relationship in medication use.